Perubahan sosial di Yogyakarta/ Selo Soemardjan ; penerjemah, Mochtar Pabotinggi; penyunting, Fadly Kurniawan - SELO SUMARJAN, 1915-2003; Mochtar Pabotinggi; Fadly Kurniawan (Komunitas Bambu, 2009)
xxxv, 502 hlm.: ilus.; 21 cm